Syntheses and transformations of azeto[2,1-a]- and -[2,1- b]isoquinolines and azeto[1 ',2 ' 1,2]pyrido[3,4-b]indoles - Fülöp Ferenc (CURRENT ORGANIC CHEMISTRY, 1999)
The syntheses, transformations and some of the biological features of azeto[2,1-a]- and -[2,1-b]isoquinolines and azeto[1',2':1,2]pyrido[3,4-b]indoles are reviewed. Both angularly and linearly fused azetidine derivatives of isoquinolines are known. As concerns the related pyridoindoles, only the angularly fused azeto[1',2':1,2]pyrido[3,4-b]indoles have been prepared and investigated. The most interesting and characteristic transformations of azetoisoquinolines and azeto[1',2':1,2]pyrido[3,4-b]indoles are the ring enlargement reactions; these result, for example, in eight-membered ring derivatives which were difficult to synthesize by earlier methods. Such derivatives are versatile intermediates for the synthesis of biologically important compounds. Some of the azetoisoquinolin-2-ones synthesized and tested to date display weak antibiotic activity. Several other azetoisoquinolines exhibit a wide range of pharmacological activities.